Preparation of manganese zinc ferrite nanoparticles by polymer matrix templated synthesis - Mohd Noor, Siti Salwa; Yaacob, Iskandar Idris (Trans Tech Publications, Switzerland, 2010)
MnxZn1-xFe2O4 nanoparticles with x = 0, 0.2, 0.4, 0.5, 0.6 and 1.0 were synthesized by polymer matrix templated synthesis. Ion exchange resins in a form of spherical beads that contained nanopores were used to precipitate the nanoparticles. The synthesized nanoparticles were characterized using several characterization techniques including X-ray diffractometry, transmission electron microscopy and alternating gradient magnetometry. XRD patterns showed that only manganese zinc ferrite nanoparticles were formed. Calculation of crystallite size from x-ray peak broadening showed that the crystallite sizes were within the range 5-11 nm. The crystallite size increased with increasing Mn concentration. TEM images showed that the particles were almost spherical with diameters ranging from 8-19 nm. Magnetization curves passed through the origin and showed no hysteresis indicated that the particles are superparamagnetic. The magnetization value at 10kOe applied magnetic field increased with increasing particle size which was mainly due to the effect of manganese content of the nanoparticles. © (2010) Trans Tech Publications.